MSME GROWTH IS BEING PROPELLED BY INDIA'S DIGITAL TRANSFORMATION - Jone, I.Arthi; C., Dhanalakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article looks at the positive relationship that exists between the growth of Micro, Small, and Medium-Sized Enterprises (MSMEs) in India and the country's digital transformation. As India adopts digital technology across all industries, MSMEs are making the most of these innovations to increase productivity, expand their market reach, and streamline operations. This research uses relevant literature reviews and empirical data analysis to help MSMEs understand the driving reasons behind India's economy's digital transformation. It highlights the way in which digitization transforms MSMEs by presenting examples of successful adoption and the subsequent growth trajectories. Additionally, the paper provides policy implications and strategic recommendations to eventually promote inclusive and sustainable economic development in India by further catalysing the positive benefits of digitalization on MSMEs.